2021
DOI: 10.1038/s43705-021-00006-2
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale sampling unveils diazotroph patchiness in the South Pacific Ocean

Abstract: Diazotrophs are important contributors to nitrogen availability in the ocean. Oceanographic cruise data accumulated over the past three decades has revealed a heterogeneous distribution of diazotroph species at regional to global scales. However, dynamic fine-scale physical structures likely affect the distribution of diazotrophs at smaller spatiotemporal scales. The interaction between fine-scale ocean dynamics and diazotrophs remains poorly understood due to typically insufficient spatiotemporal sampling res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The enhancement of diatom and meso-zooplankton abundance at fronts found here is supported by a handful of targeted in-situ studies in various parts of the globe, for instance in the Kuroshio Extension Front (which is a WBC similar to our model, Clayton et al, 2014), the Iceland-Faeroe Front in the North Atlantic (Allen et al, 2005), the Almeria-Oran Front in the Mediterranean Sea (Claustre et al, 1994;Thibault et al, 1994;Hernández-Carrasco et al, 2020) and fronts in the California Current Ecosystem (Taylor et al, 2012;Ohman et al, 2012). In contrast, observations of the other groups of plankton are sparse and often inconclusive and contradictory (Benavides et al, 2021;Clayton et al, 2017). This concurs with results from this model study which suggests some indirect responses such as community shading and shared predation can lead to more complex responses in the less opportunist species.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The enhancement of diatom and meso-zooplankton abundance at fronts found here is supported by a handful of targeted in-situ studies in various parts of the globe, for instance in the Kuroshio Extension Front (which is a WBC similar to our model, Clayton et al, 2014), the Iceland-Faeroe Front in the North Atlantic (Allen et al, 2005), the Almeria-Oran Front in the Mediterranean Sea (Claustre et al, 1994;Thibault et al, 1994;Hernández-Carrasco et al, 2020) and fronts in the California Current Ecosystem (Taylor et al, 2012;Ohman et al, 2012). In contrast, observations of the other groups of plankton are sparse and often inconclusive and contradictory (Benavides et al, 2021;Clayton et al, 2017). This concurs with results from this model study which suggests some indirect responses such as community shading and shared predation can lead to more complex responses in the less opportunist species.…”
Section: Discussionsupporting
confidence: 56%
“…Other observations have shown that fronts can favor the coexistence of different taxa of phytoplankton (Ostreococcus eco-types in the Kuroshio Extension front Clayton et al, 2017 or on the contrary separate them on either side (Prochlorococcus and Synechococcus in a front in the California Current Ecosystem Taylor et al, 2012). The enhancement of other groups of phytoplankton at fronts, such as the diazotroph Trichodesmium in coherent frontal filaments in the South Pacific (Benavides et al, 2021), has also been reported. The increased abundance and production of some zooplankton groups, especially copepods, has also been recorded in a few studies (Ohman et al, 2012;Luo et al, 2014).…”
Section: Introductionmentioning
confidence: 88%
“…In some oceanographic observations, regions of velocity convergence have been shown to result in accumulation of phytoplankton populations. For example, convergence has been observed to impact biological populations in a coastal region of the Western Mediterranean Sea (Hernández‐Carrasco et al., 2018) and in open ocean regions (Benavides et al., 2021; Guidi et al., 2012; Palter et al., 2020). These convergence zones may hold particular biogeochemical significance because they disproportionately cause accumulation of buoyant phytoplankton such as nitrogen‐fixers (Benavides et al., 2021; Palter et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of the role of lateral advection and its association with the El Niño can help us better understand the structure and function of the marine ecosystem in the context of climate change. To obtain a comprehensive understanding of the phytoplankton community response to climate‐driven Kuroshio intrusion of marginal seas, long‐term continuous observation should be established (Benavides et al., 2021).…”
Section: Discussionmentioning
confidence: 99%